Semicarbazide-Sensitive Amine Oxidase Increases in Calcific Aortic Valve Stenosis and Contributes to Valvular Interstitial Cell Calcification. (14th January 2020) - Mercier, Nathalie; Pawelzik, Sven-Christian; Pirault, John; Carracedo, Miguel; Persson, Oscar; Wollensack, Bastien; Franco-Cereceda, Anders; Bäck, Magnus
Abstract : Introduction. Calcific aortic valve stenosis (CAVS) is a common disease associated with aging. Oxidative stress participates in the valve calcification process in CAVS. Semicarbazide-sensitive amine oxidase (SSAO), also referred to as vascular adhesion protein 1 (VAP-1), transforms primary amines into aldehydes, generating hydrogen peroxide and ammonia. SSAO is expressed in calcified aortic valves, but its role in valve calcification has remained largely unexplored. The aims of this study were to characterize the expression and the activity of SSAO during aortic valve calcification and to establish the effects of SSAO inhibition on human valvular interstitial cell (VIC) calcification. Methods . Human aortic valves from n = 80 patients were used for mRNA extraction and expression analysis, Western blot, SSAO activity determination, immunohistochemistry, and the isolation of primary VIC cultures. Results . SSAO mRNA, protein, and activity were increased with increasing calcification within human aortic valves and localized in the vicinity of the calcified zones. The valvular SSAO upregulation was consistent after stratification of the subjects according to cardiovascular and CAVS risk factors associated with increased oxidative stress: body mass index, diabetes, and smoking. SSAO mRNA levels were significantly associated with poly(ADP-ribose) polymerase 1 (PARP1) in calcified tissue. Calcification of VIC was inhibited in the presence of the specific SSAO inhibitor LJP1586. Conclusion . The association of SSAO expression and activity with valvular calcification and oxidative stress as well as the decreased VIC calcification by SSAO inhibition points to SSAO as a possible marker and therapeutic target to be further explored in CAVS.